A Study about the Power System Effect by Load Following of Nuclear Power Governor Control - Lee, Hyun-Chul; Roh, Young-Gi; Jung, Byoung-Jo (International Journal of Engineering and Technology, 2018)
Background/Objectives: Nuclear power generator has no emission of CO2 and has been presented as a practical alternative to prepare for climate change conversions and to promote energy independence.Methods/Statistical analysis: The load pattern was analyzed using the power system prediction data of 2024 year. Nuclear power system analysis has been changed the governor operating rate within the rage of acceptable performance by the speed droop of standards, in consideration of the safety of the power plant. The frequency variation limit has been evaluated the power system by applying the N-2 generator contingency.Findings: The system frequency should be constantly output when the load fluctuates. However, large load fluctuation was occurred according to the power system frequency was deviate from the operating standard. The frequency recovery of the power system reference for stable system operation reduces the frequency fluctuation by securing reserve power of the generation. Nuclear power generation was used to secure large capacity reserves. The control of nuclear power has been studied by used governor control.Improvements/Applications: It was possible to obtain coast-effective results than the hydro-generator operation of the momentary reactive reserve for conventional governor droop control. Nuclear power could be controlled by various operating methods, and could be used as friendly environment energy through reduction of CO2 in the environment side.Â Â